2017
DOI: 10.1016/j.jinsphys.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress in tomato increases the performance of adapted and non-adapted strains of Tetranychus urticae

Abstract: The performance of the two-spotted spider mite, Tetranychus urticae Koch, on plants depends on the rate of adaptation of mite populations to each particular host and can be influenced by environmental conditions. We have tested the effects of drought stress, caused by water deficiency, in the interaction of tomato plants with tomato adapted (TA) and tomato non-adapted (TNA) strains of T. urticae. Our data revealed that mite performance was enhanced for the TA strain when reared on drought-stressed tomato plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 39 publications
7
38
1
Order By: Relevance
“…T. urticae is a cosmopolitan pest that feeds on more than 1,100 documented plant species, of which 150 are important agronomic crops [11]. Besides, under the current climate change scenario associated with dry and hot conditions, T. urticae shortens its life cycle, produces more generations per year and broadens the host range [12]. Spider mites feed, mainly but not only, on the leaves by piercing individual mesophyll cells.…”
Section: Introductionmentioning
confidence: 99%
“…T. urticae is a cosmopolitan pest that feeds on more than 1,100 documented plant species, of which 150 are important agronomic crops [11]. Besides, under the current climate change scenario associated with dry and hot conditions, T. urticae shortens its life cycle, produces more generations per year and broadens the host range [12]. Spider mites feed, mainly but not only, on the leaves by piercing individual mesophyll cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, this interaction has been shown to be more complex since it also depends on the plant species, the intensity and duration of the drought stress and the arthropod feeding mechanism [ 30 , 31 ]. Previous results coming from the analysis of the interaction between T. urticae or T. evansi and moderate water stress conditions in tomato plants (cv Moneymaker) showed the increase of both spider mite populations, thus confirming the modification of the plant–spider mite interaction under water stress conditions [ 21 , 32 , 33 ]. Moreover, the characterization of the T. evansi attack to traditional drought-tolerant tomato varieties has shown that adaptation of tomato plants to moderate drought modifies physiological plant responses to tomato red spider mite associated with an increase of tomato ABA levels [ 21 ].…”
Section: Introductionmentioning
confidence: 58%
“…Previous identification of tomato metabolic changes to moderate water deficit by biochemical and targeted metabolite profiling have shown a significant variation in amino acids and sugar composition, which may increase the nutritional value of the tomato plants leading to increase the leaf damage and oviposition of T. evansi in tomato drought-stressed plants [ 21 , 32 , 33 ]. To increase knowledge on the plant metabolites produced during concurring T. evansi attack and moderate drought stress on tomato, a non-targeted metabolite profiling of semi-polar metabolites was conducted using UPLC/ESI-QTOF-MS in positive and negative ion modes.…”
Section: Resultsmentioning
confidence: 99%
“…Plants exposed to abiotic stressors, such as drought and nutrient deficiencies, are often more susceptible to biotic stressors. This holds true for a large variety of arthropod pests, such as spider mites (Garman and Kennedy 1949, Rodriguez and Neiswander 1949, Rodriguez 1951, Perring et al 1986, Stiefel et al 1992, Machado et al 2000, Abdel-Galil et al 2007, Nansen et al 2013, Ximénez-Embún et al 2017, aphids (Myers and Gratton 2006, Walter and Difonzo 2007, Lacoste et al 2015, and lepidopteran larvae (Gutbrodt et al 2011(Gutbrodt et al , 2012Grinnan et al 2013;Weldegergis et al 2015). Due to this well-established association between abiotic stressors and risk of arthropod pest outbreaks, it may be argued that precision application of abiotic stress relief, such as application of water and fertilizer, represents a meaningful approach to reducing the risk of outbreaks by some arthropod pests (Nansen et al 2013, West andNansen 2014).…”
Section: Pest Outbreak Preventionmentioning
confidence: 98%